Analyzing the Influence of UTAUT2 Constructs and E-Commerce Usage Frequency on Gen Z's Purchase Intention Toward AR Virtual Try-On Shade Filters - Ayu Jesica Swaharani; Annisa Rahmani Qastharin (Pusat Riset dan Inovasi Nasional, 2025)
The rapid growth of Indonesia’s beauty and e-commerce industries has fueled the adoption of Augmented Reality (AR) virtual try-on (VTO) shade filters, particularly for makeup products such as lipstick and foundation. These tools enable users to visualize products before purchasing, addressing a major challenge in online beauty shopping. While Gen Z consumers are highly active in digital environments, research on how AR VTO shade features influence their buying decisions remains limited. This study applies the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) to examine the impact of each UTAUT2 construct on purchase intention among Indonesian Gen Z consumers when using AR try-on shade filters on e-commerce platforms. It also investigates whether e-commerce usage frequency moderates these effects. A quantitative method was employed, with data collected from 260 female Gen Z respondents and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM). Findings reveal that all seven UTAUT2 constructs—Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, and Habit—significantly influence purchase intention, with Habit emerging as the strongest predictor. Moreover, e-commerce usage frequency was found to moderate these relationships. Among frequent users, the effects of Performance Expectancy, Facilitating Conditions, Hedonic Motivation, and Price Value on purchase intention were stronger, while the influence of Effort Expectancy, Social Influence, and Habit was weaker. The results confirm that UTAUT2 effectively explains AR adoption in e-commerce beauty contexts. The study suggests that businesses should tailor AR strategies according to users’ e-commerce experience levels to enhance engagement, strengthen purchase intentions, and optimize the effectiveness of AR integration. Such adjustments can help e-commerce platforms provide more personalized and immersive shopping experiences, ultimately boosting customer satisfaction and sales performance.